2013
DOI: 10.3176/eco.2013.3.03
|View full text |Cite
|
Sign up to set email alerts
|

The role of railway lines in the distribution of alien plant species in the territory of Daugavpils City (Latvia)

Abstract: The study was performed based on an inventory of alien flora in Daugavpils City. During the field studies all the alien species were recorded applying a regular grid consisting of 344 quadrats of 500 m × 500 m. Data of the 84 quadrats that cover all railway lines in the city were analysed to identify relationships between the distribution of alien plants and the location of railway lines. First the obtained data were compared with the first flora inventory in the city, which was conducted from 1975 to 1983. Co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 25 publications
1
14
0
Order By: Relevance
“…The coldest months are January and February, their average temperatures are -4.6 and -4.7 °C, respectively. The absolute maximum temperature, + 36.4 °C, and the absolute minimum temperature, -43.2 °C, in the whole territory of Latvia were observed only in Daugavpils; thus the range of extreme temperatures here is 79.6 °C Rutkovska et al, 2013). The average annual precipitation is 667 mm.…”
Section: Study Areamentioning
confidence: 96%
“…The coldest months are January and February, their average temperatures are -4.6 and -4.7 °C, respectively. The absolute maximum temperature, + 36.4 °C, and the absolute minimum temperature, -43.2 °C, in the whole territory of Latvia were observed only in Daugavpils; thus the range of extreme temperatures here is 79.6 °C Rutkovska et al, 2013). The average annual precipitation is 667 mm.…”
Section: Study Areamentioning
confidence: 96%
“…Abandoned areas such as railway embankments and freight yards, where plant species grow without control, can be important for their high floristic diversity (Zerbe et al 2003;Herbst and Herbst 2006). Moreover, highways and railways often act as ecological corridors for the spread and establishment of native (Penone et al 2012) and non-native (Hansen and Clevenger 2005;Wilkomirski et al 2012; Barina et al 2013;Rutkovska et al 2013) plant species, especially neophytes, with new arrivals almost every year (e.g. Ardenghi 2013).…”
Section: Introductionmentioning
confidence: 98%
“…The disturbed area is particularly important during the early stage of invasion because it creates vacant niches that alien plants can colonise (Masters & Sheley 2001). Rutkovska et al (2013) found that some of the alien taxa in Latvia were associated with topsoil disturbance because of the construction and maintenance of railway lines. It is therefore possible that the development of railway networks in the study area may have promoted the distribution and spread of some of the alien plants.…”
Section: Limitations Of the Satellite Imagementioning
confidence: 99%
“…The Southern African Plant Invaders Atlas (SAPIA) database (2016) provides information on railway side invasion in certain areas of South Africa, including parts of the Mpumalanga province. Woody alien plants along railway sides are a concern to railway infrastructure and rail operations because dense infestations often conceal railway crossings, endangering human life (Rutkovska et al 2013). Infestations along railways may also act as a starting point for the spread of species to the neighbouring agricultural or natural landscape.…”
Section: Introductionmentioning
confidence: 99%